SAIKAT: A NEW POTATO VARIETY FOR COASTAL AREAS OF BANGLADESH - Rashid, M. H.; Hossain, M. M.; Hossain, M; Mahmud, A. A.; Akhtar, M. I; Kadian, M. S; Chujoy, E; Bonierbale, M.; Ilangantileke, S (Potato Journal, 2013)
The potato variety Provento from Netherlands, and CIP (International Potato Center) clone 88.163 were evaluated for commercial cultivation in Bangladesh. In respect of yield and other qualities, both the genotypes were at par with the standard popular Dutch varieties Diamant and Cardinal. The CIP clone 88.163 named as â€œSaikatâ€ (meaning sea shore) is recommended for cultivation in coastal areas of the country. â€˜Saikatâ€™ was superior to the check varieties in respect of resistance to late blight and virus diseases, and keeping quality under natural conditions.